Turning Macro-appraisal Decisions into Archival Holdings: Crafting Function-based Terms and Conditions for the Transfer of Archival Records - Bailey, Catherine A. (Archivaria, 2006)
Since the National Archives of Canada (now Library and Archives Canada) introduced macroappraisal in 1990, its government records archivists have sought to create terms and conditions for the transfer of archival records based on functions and activities. In 2003, the NA/LAC Terms and Conditions Work Group (TCWG) bridged the divide between appraisal and acquisition by developing the necessary methodology to translate an archivist’s macro-appraisal decisions into disposition tools (the formal Terms and Conditions for the Transfer of Archival Records within the Records Disposition Authority, as well as a complementary Application Guide) that would ensure the identification and selection of archival records in all media. This article places the work of the TCWG within the context of the evolution of federal government record-keeping and macro-appraisal methodology as applied within LAC, and presents an overview of the disposition tools that it produced. RÉSUMÉ Depuis que les Archives nationales du Canada (dorénavant Bibliothèque et Archives Canada) ont introduit la pratique de la macro-évaluation en 1990, leurs archivistes responsables des documents gouvernementaux ont tenté d’établir des conditions et des modalités de transfert pour les documents d’archives en tenant compte de l’analyse fonctionnelle. En 2003, le groupe de travail des modalités de transfert (GTMT) des AN/BAC a fait le lien entre l’évaluation et l’acquisition en élaborant la méthodologie nécessaire pour assurer que les décisions de l’archiviste découlant de la macro-évaluation se traduisent en une documentation pour disposer des documents (les conditions et les modalités pour le transfert de documents archivistiques dans l’autorisation de disposer des documents, ainsi que le guide d’application complémentaire). Ces outils permettent aux archivistes d’assurer l’identification et la sélection de documents d’archives dans tous les médias. Cet article situe le travail du GTMT dans le contexte de l’évolution de la gestion des documents du gouvernement fédéral et de la méthodologie de la macro-évaluation telle qu’elle est employée à BAC, puis il présente un survol de la documentation produite par le GTMT pour disposer des documents.